Nanotoxicity of poly(n-butylcyano-acrylate) nanoparticles at the blood-brain barrier, in human whole blood and in vivo - Kolter, Marise; Ott, Melanie; Hauer, Christian; Reimold, Isolde; Fricker, Gert (Journal of controlled release, 2015)
Therapy of diseases of the central nervous system is a major challenge since drugs have to overcome the blood-brain barrier (BBB). A powerful strategy to enhance cerebral drug concentration is administration of drug-loaded poly(n-butylcyano-acrylate) (PBCA) nanoparticles coated with polysorbate 80 (PS80). This study evaluates the toxicity of PBCA-nanoparticles at the BBB, representing the target organ, the inflammatory response in human whole blood, as the site of administration and in a rat model in vivo.
Available online 10 November 2014
Gesehen am 15.07.2020